COVID-19 and psychosis risk: Real or delusional concern?. (10th January 2021) - Watson, Cameron J.; Thomas, Rhys H.; Solomon, Tom; Michael, Benedict Daniel; Nicholson, Timothy R.; Pollak, Thomas A.
Highlights: Viruses and immune function have been associated with psychosis through genetic and epidemiological research. We critically evaluate the case for psychosis in COVID-19 through analysis of reported cases and historical precedents. Potential infectious, post-infectious and neurodevelopmental aetiologies are explored. Further appraisal of potential neurobiological and psychosocial mechanisms of 'COVID-19 psychosis' is urgently needed. Abstract: Historical epidemiological perspectives from past pandemics and recent neurobiological evidence link infections and psychoses, leading to concerns that COVID-19 will present a significant risk for the development of psychosis. But are these concerns justified, or mere sensationalism? In this article we review the historical associations between viral infection and the immune system more broadly in the development of psychosis, before critically evaluating the current evidence pertaining to SARS-CoV-2 and risk of psychosis as an acute or post-infectious manifestation of COVID-19. We review the 42 cases of psychosis reported in infected patients to date, and discuss the potential implications of in utero infection on subsequent neurodevelopment and psychiatric risk. Finally, in the context of the wider neurological and psychiatric manifestations of COVID-19 and our current understanding of the aetiology of psychotic disorders, we evaluate possible neurobiological and psychosocial mechanisms as well as the numerous challenges in ascribing a causal pathogenic role to the infection.